2020
DOI: 10.4317/medoral.23519
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of BRAF V600E mutation in Iranian population ameloblastomas

Abstract: Background Ameloblastoma is a common locally invasive but slow-growing neoplasm of the jaws with an odontogenic origin. Association between BRAF V600E mutation and clinicopathologic features and behavior of ameloblastoma remains controversial. This study aimed to evaluate BRAF V600E gene mutation and expression of its related proteins with clinicopathologic parameters in conventional ameloblastoma. Material and Methods 50 Formalin-fixed paraffin-embedded blocks were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 26 publications
1
19
2
Order By: Relevance
“… 56 The disadvantages of each technique make the accuracy and the comparative analyses unreliable. Some authors reported an adequate agreement, 13 , 16 , 17 , 19 , 22 , 34 , 36 , 38 , 50 whereas others showed a high results variability between the detection methods. 15 , 20 , 26 , 29 , 37 , 41 , 49 Especially, a low sensitivity and a high specificity of immunohistochemistry have been demonstrated.…”
Section: Discussionmentioning
confidence: 97%
“… 56 The disadvantages of each technique make the accuracy and the comparative analyses unreliable. Some authors reported an adequate agreement, 13 , 16 , 17 , 19 , 22 , 34 , 36 , 38 , 50 whereas others showed a high results variability between the detection methods. 15 , 20 , 26 , 29 , 37 , 41 , 49 Especially, a low sensitivity and a high specificity of immunohistochemistry have been demonstrated.…”
Section: Discussionmentioning
confidence: 97%
“…In 2014, the pioneer study by the group of Heikinheimo reported for the first time recurrent activating BRAF p.V600E mutations in ameloblastomas [9]. Considering that MAPK/ERK signaling can be activated by stimulation of transmembrane receptors, including EGFR, and that overexpression of EGFR had previously been reported in ameloblastomas, when [9], [10], [51], [52], [53] e , [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [ V600E mutation in all five ameloblastic carcinoma samples evaluated and this frequency was much higher than reported by previous studies, and therefore we did not add the results to the other ones when calculating mutation frequency.…”
Section: Ameloblastomamentioning
confidence: 99%
“…They further reported the presence of BRAF p.V600E mutation in 67% (23/34) of ameloblastomas by using VE1 immunohistochemistry in cases not suitable for molecular evaluation [52]. Following these pieces of research, several studies have also assessed the presence of BRAF p.V600E in conventional ameloblastoma, either by molecular techniques or a combination of mutation screening and immunohistochemistry, with mutation frequencies varying from 55 to ∼90% [10,[53][54][55][56][57][58][59][60][61][62][63]. In two studies with limited sample numbers, the mutation was detected in all samples [2/2 [64] and 4/4 [65]].…”
Section: Ameloblastomamentioning
confidence: 99%
“…[9][10][11] This mutation induces homeostatic activation of BRAF, which activates the RAF-MEK-ERK pathway and enhances the proliferative potential of tumor cells. The presence and prevalence of the BRAF V600E mutation in ameloblastoma have been reported in patients from various regions 6,7,[12][13][14][15][16][17][18] ; it ranges from 42.9% to 92.0%. In our study, the mutation was detected at a higher rate, that is, 83% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the false positive rate reported in the evaluation of BRAF mutations, using immunohistochemical staining with the VE1 antibody. 16,18,22 This could be attributed to sampling problems. Small tumor foci could be insufficient for PCR-based detection.…”
Section: Discussionmentioning
confidence: 99%